Bone loss in the contralateral asymptomatic hand in patients with complex regional pain syndrome type 1 - Karacan, Ilhan; Aydin, Teoman; Ozaras, Nihal (Journal of bone and mineral metabolism, 2004)
Regional osteoporosis was seen radiographically in clinically affected areas in patients with complex regional pain syndrome type 1 (CRPS1). The aim of the this study was to investigate whether bone loss developed in the contralateral hand in patients with unilateral CRPS1 of the hand. Thirty-two patients with CRPS1 of the hand were included in this study. Bone mineral density was measured in the left proximal femur and both ultradistal radiuses, using dual-energy X-ray absorptiometry. The subjects were classified as grades 1 to 3 according to the T-score of both ultradistal radiuses (densitometric grades): grade 1, both radiuses were normal; grade 2, bone loss was determined only in the affected radius; and grade 3, there was bone loss in both radiuses. Twenty (62.5%) patients had bone loss in the affected hand; 11 patients (34.4%) had bone loss only on the affected side and 9 patients (28.1%) had bone loss on both sides. The mean duration of the period between the diagnosis of the injury and the measurement of bone density was 1.9 +/- 0.6 months in patients with grade 1, 3.1 +/- 1.0 months in patients with grade 2, and 5.5 +/- 2.2 months in patients with grade 3. The Spearman test showed a significant correlation between the period of injury and the densitometric grade ( R = 0.774; P = 0.0001). In conclusion, the current study of patients with CRPS1, showed that the bone loss in the asymptomatic contralateral hand developed at a later stage than that in the affected hand. This bone loss was less frequent and of a lower degree in the asymptomatic contralateral hand than in the affected hand. The bone loss in the asymptomatic contralateral hand could be explained by the loss of sympathetic tone in CRPS1 and contralateral sympathetic innervation.